EL «CHINO» Y EL «INDIO»: PEDRO S. ZULEN Y JULIO C. TELLO, UNA AMISTAD DEL NOVECIENTOS A TRAVES DE SU CORRESPONDENCIA, 1914- 1922 - del Castillo Morán, Miguel Ángel (2002)
The present article is about the relationship between the two important intellectual and indigenistas limeños ofthe «nineteenth century» generation. The authors joins, as an appendix, the correspondence exchanged by each other in the lapse ofeight years.